Causal relationships of familial hypercholesterolemia with the risk of multiple vitamin deficiencies: a Mendelian randomization study - Zhang, Cheng; Wei, Gang; Zhou, Huan; Liu, Lin (Frontiers in Endocrinology, 2024)
Background The causal relationship between familial hypercholesterolemia (FH) and various vitamin deficiencies has not yet been elucidated. Therefore, this study investigated the cause-and-effect relationship between FH and the risk of multiple vitamin deficiencies in humans. Methods Mendelian randomization (MR) analysis was performed by extracting six datasets for FH, FH with ischemic heart disease (IHD), and vitamin deficiency (vitamin A, thiamine, other B-group vitamins, and vitamin D) from the FinnGen study, covering a total of 329,115; 316,290; 354,932; 354,949; 355,411 and 355,238 individuals, respectively. Results FH was suggestively associated with higher odds of thiamine deficiency [inverse variance weighted odds ratio (ORIVW) 95% confidence interval (CI): 1.62 (1.03, 2.55), P = 0.036] and vitamin D deficiencies [ORIVW CI: 1.35 (1.04, 1.75), P = 0.024], low-density lipoprotein receptor (LDLR) rs112898275 variant, rs11591147 and rs499883 in proprotein convertase subtilisin/kexin 9 (PCSK9), rs9644862 in cyclin-dependent kinase inhibitor 2 B antisense RNA1 (CDKN2B-AS1), and rs142834163 in dedicator of cytokinesis 6 (DOCK6) and rs115478735 in ABO blood group (ABO) strongly influenced the risk of thiamine deficiency, while the rs7412 variant in apolipoprotein E (APOE) mostly influenced the risk of vitamin D deficiency. FH with IHD was suggestively associated with higher odds of vitamin D deficiency (ORIVW, weighted median [WM][95%CI]: 1.31 [1.05, 1.64]; 1.47 [1.10, 1.97]) (P = 0.018; 0.010) without any single significant SNPs observed. Conclusion FH was positively associated with increased risks of thiamine and vitamin D deficiencies, revealing a prospective and unfortunate complication of FH.